FINES AND DAILY FINES UNDER THE ACT ON THE AMENDMENTS TO COMPETITION ACT WITH SPECIAL EMPHASIS ON MITIGATING AND AGGRAVATING CIRCUMSTANCES (EU and comparative law issues and challenges series (ECLIC), 2021)
The paper analyzes the amendments to Title VIII of the Croatian Competition Act regulating penalty clause or the fines, daily fines, and the methods for their imposition, adopted in April 2021. Daily fines are a new institute that further extends the Croatian Competition Agency's (CCA) power as a general, national regulatory authority responsible for the protection of competition in all markets. Therefore, each amended article of that Title is analysed to accurately reflect what has changed and with which provision of the Directive (EU) 2019/1 it has been harmonized. The paper also provides a detailed tabular overview and comparison of the amount of the fine and mitigating and aggravating circumstances that the Agency considered into account when imposing them in cases in the period from 2013 to the end of 2020, so that, finally, it can be concluded if there is a consistent relationship between the number of mitigating and aggravating circumstances and the amount of the fine that CCA imposes when there are infringements of the national and EU competition law.